2016
DOI: 10.21511/ppm.14(4-1).2016.04
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of skills development transfer on organizational commitment – a case-study of Free State TVET colleges

Abstract: One of the legacies of Apartheid South Africa which has ominous consequences for the economy, is the insidious dire skills shortage for majority of the citizens. Compelling government to embark on an intensive wholesale skills development to ameliorate and stimulate the general economic performance. This paper therefore, explored the relationship between employee organizational commitment and skills development transfer. A longitudinal study, with a pre-and post-quasi experimental research design was adopted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The results further revealed that job fulfilment moderated the relationship between access to educational opportunities and the affective job commitment of workers (Bartlett, 2001). Various studies have also revealed a significant association (correlation) between training/retraining on staff job commitment in schools after adopting different methodologies (Mackenzie & Nwafor, 2019;Naong, 2016).…”
Section: Staff Retraining and Educators' Job Commitmentmentioning
confidence: 84%
“…The results further revealed that job fulfilment moderated the relationship between access to educational opportunities and the affective job commitment of workers (Bartlett, 2001). Various studies have also revealed a significant association (correlation) between training/retraining on staff job commitment in schools after adopting different methodologies (Mackenzie & Nwafor, 2019;Naong, 2016).…”
Section: Staff Retraining and Educators' Job Commitmentmentioning
confidence: 84%
“…Diversity in South Africa is complex and often associated with conflicts and distrust that make it difficult to manage [79]. Apartheid and the resulting skills shortage have affected people from designated groups [81], evoking the diversity agenda in the workplace. Although there are legislative mandates to promote gender representation at the top levels, management often approaches gender equity as a compliance issue [34] without a conscious desire to see change.…”
Section: Sexual Harassmentmentioning
confidence: 99%
“…This means that the growth and success of the TVET college sector are fundamental to advancing economic and social well-being. Furthermore, they emphasize the need to expand the role of TVET college sector education in a democratic developmental state (Naong, 2016). They argue that it should not only focus on traditional educational goals but also address broader national social and economic objectives.…”
Section: The Impact Of Tvet On Education and Skill Developmentmentioning
confidence: 99%